Selective Cytotoxicity of Damsin Derivatives in Breast Cancer Cells - Maribel Lozano; Wendy Soria; Giovanna R. Almanza; Sophie Manner; Stina Oredsson; Rodrigo Villagomez; Olov Sterner (Journal of Advanced Pharmaceutical Science And Technology, 2019)
Cancer is the leading cause of death worldwide, and there is a constant need for new treatment strategies. Sesquiterpene lactones containing a 3-methylenedihydrofuran-2(3H)-one (or α-methylene-γ-lactone) moiety, for example damsin (1), are Michael acceptors that affect biological processes such as cell proliferation, death/apoptosis, and cell migration, by interfering with cell signalling pathways. Although the reactivity of the α-methylene-γ-lactone moiety is important for these effects, the Michael addition is reversible and it can be assumed that also other parts of the molecules will moderate any given biological activity. In this investigation, the cytotoxicity of 23 -methylene--lactones towards normal breast epithelial MCF-10A cells as well as breast cancer JIMT-1 cells is compared. Most of the investigated compounds are semisynthetic derivatives prepared by the condensation of the natural product damsin (1) with aldehydes. The two cell lines were treated with various concentrations of the compounds in dose response assays, and the 50 % inhibitory concentration (IC50) was determined from dose response curves. The IC50 values were found to depend strongly on the overall structure. The ratio between the IC50 values for MCF-10A and JIMT-1 cells, as a measure for the selectivity of a compound to kill cancer cells, was calculated, and found to vary between just over 1 to more than 10. The most potent derivatives formed from the condensation of 1 with aromatic aldehydes towards JIMT-1 cells are 3a and 3i, both with ratios between the IC50 values for MCF-10A and JIMT-1 cells close to 5. Also some aldol condensation products with acyclic aldehydes, i.e. 3r and 3u, were equally potent, and the latter showed the highest selectivity (ratio > 10). Structure-activity relationships that may explain the observed differences in potency and selectivity are discussed.
Keywords: MCF-10A